Prediction of Oesophageal Varices by Liver Right Lobe Diameter to Serum Albumin Ratio Among Patients With Cirrhosis of Liver - Ullah, Parash; Aftab, Hafeza; Ara Keya, Shamim; Podder, Mrinmay Kumar; Rahman, Sk Mahmudur; Bashar, Khondaker Abul; Hossain, Md Imran; Rahman, Md Mustafezur; Rahman Mia, Md Moshiur; Rahman, Md Mahmudur (Bangladesh Journal of Medicine, 2022)
Background: Oesophageal varix is one of the major complications of liver cirrhosis. Repeated endoscopic examinations are unpleasant for patients and also have cost impact. The aim of the study was to determine the predictive value of liver right lobe diameter to serum albumin ratio, a non-invasive parameter for the prediction of esophageal varices. Methods: A Cross-sectional observational study was carried out on cirrhotic patients in Gastroenterology department, Dhaka Medical College Hospital, Dhaka. Patients were subjected to complete blood picture, liver functions, viral markers; abdominal ultrasonography, upper gastrointestinal endoscopy and calculation of the Liver right lobe diameter to serum albumin ratio were done. Statistical analysis was done using SPSS software version 23. Results: A total number of 80 patients were included. Age of the patient (mean ± SD) was 47.00±14.53 years, while 57(71%) were men. Regarding etiology, 40(50%) patients had HBV and 10(12.5%) in HCV. Child-Turcotte-Pugh grades showed 54(67.5%) had CTP grade B, followed by 23(28.7%) grade A. Esophageal varices were observed in 65(81%) of the patients. The mean liver right lobe diameter to albumin ratio was 4.5±0.57 in patients having oesophageal varices and 3.9±0.27 in patients without oesophageal varices which was statistically significant (p values 0.01). The best cut off value of liver right lobe diameter to serum albumin was determined at the highest point of Youden index, which was 4.16. With this cut off value, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy was 73.8 %, 60.6 %, 88.8 %, 34.6% and 71.2% respectively. Conclusion: This ratio is a useful noninvasive predictor for the presence of oesophageal varices but cannot be advocated clinically due to low sensitivity and specificity. It may serve for selection of patient who need urgent endoscopy and helps when endoscopy facilities are limited or contraindicated or restricted like Covid-19 pandemic situation. Bangladesh J Medicine 2022; 33: 18-23